Low Serum 25-hydroxyvitamin D (Vitamin D) Level Is Associated With Susceptibility to COVID-19, Severity, and Mortality: A Systematic Review and Meta-Analysis - Akbar, Mohammad Rizki; Wibowo, Arief; Pranata, Raymond; Setiabudiawan, Budi (Frontiers in Nutrition, 2021)
Background This systematic review and meta-analysis aimed to assess whether low serum 25-hydroxyvitamin D (25-OHD) level is associated with susceptibility to COVID-19, severity and mortality related to COVID-19. Methods Systematic literature searches of PubMed, Scopus, and Embase database up until 9 December 2020. We include published observational prospective and retrospective studies with information on 25-OHD that reported main/secondary outcome. Low serum 25-OHD refers to participants with serum 25-OHD level below a cut-off point ranging from 20 to 30 ng/mL. Other cut-off values were excluded to reduce heterogeneity. The main outcome was mortality defined as non-survivor/death. The secondary outcome was susceptibility and severe COVID-19. Results There were 14 studies comprising of 999,179 participants. Low serum 25-OHD was associated with higher rate of COVID-19 infection compared to the control group (OR 2.71 [1.72, 4.29], p<0.001; I2: 92.6%). Higher rate of severe COVID-19 was observed in patients with low serum 25-OHD (OR 1.90 [1.24, 2.93], p=0.003; I2: 55.3%), with a sensitivity of 83%, specificity of 39%, PLR of 1.4, NLR of 0.43, and DOR of 3. Low serum 25-OHD was associated with higher mortality (OR 3.08 [1.35, 7.00], p=0.011; I2: 80.3%), with a sensitivity of 85%, specificity of 35%, PLR of 1.3, NLR of 0.44, and DOR of 3. Meta-regression analysis showed that the association between low serum 25-OHD and mortality was affected by male gender (OR 1.22 [1.08, 1.39], p=0.002), diabetes (OR 0.88 [0.79, 0.98], p=0.019). Conclusion Low serum 25-OHD level was associated with COVID-19 infection, severe presentation, and mortality.